Pseudomonas putida mt-2 tolerates reactive oxygen species generated during matric stress by inducing a major oxidative defense response. Issue 1 (December 2015) - Svenningsen, Nanna; Pérez-Pantoja, Danilo; Nikel, Pablo; Nicolaisen, Mette; de Lorenzo, Víctor; Nybroe, Ole
Abstract Background Soil bacteria typically thrive in water-limited habitats that cause an inherent matric stress to the cognate cells. Matric stress gives rise to accumulation of intracellular reactive oxygen species (ROS), which in turn may induce oxidative stress, and even promote mutagenesis. However, little is known about the impact of ROS induced by water limitation on bacteria performing important processes as pollutant biodegradation in the environment. We have rigorously examined the physiological consequences of the rise of intracellular ROS caused by matric stress for the toluene- and xylene-degrading soil bacteriumPseudomonas putida mt-2. Methods For the current experiments, controlled matric potential stress was delivered toP. putida cells by addition of polyethylene glycol to liquid cultures, and ROS formation in individual cells monitored by a specific dye. The physiological response to ROS was then quantified by both RT-qPCR of RNA transcripts from genes accredited as proxies of oxidative stress and the SOS response along with cognate transcriptional GFP fusions to the promoters of the same genes. Results Extensive matric stress at −1.5 MPa clearly increased intracellular accumulation of ROS. The expression of the two major oxidative defense geneskatA andahpC, as well as the hydroperoxide resistance geneosmC, was induced under matric stress. Different induction profiles of the reporters were related to the severity of the stress. To determine if matric stress lead to induction of the SOS-response, we constructed a DNA damage-inducible bioreporter based on the LexA-controlled phage promoter PPP3901 . According to bioreporter analysis, this gene was expressed during extensive matric stress. Despite this DNA-damage mediated gene induction, we observed no increase in the mutation frequency as monitored by emergence of rifampicin-resistant colonies. Conclusions Under conditions of extensive matric stress, we observed a direct link between matric stress, ROS formation, induction of ROS-detoxifying functions and (partial) activation of the SOS system. However, such a stress-response regime did not translate into a general DNA mutagenesis status. Taken together, the data suggest thatP. putida mt-2 can cope with this archetypal environmental stress while preserving genome stability, a quality that strengthens the status of this bacterium for biotechnological purposes.